Reading two bases twice: mammalian antizyme frameshifting in yeast. - Matsufuji, S (1996)
Programmed translational frameshifting is essential for the expression of mammalian ornithine decarboxylase antizyme, a protein involved in the regulation of intracellular polyamines. A cassette containing antizyme frameshift signals is found to direct high-level (16%) frameshifting in yeast, Saccharomyces cerevisiae. In contrast to +1 frameshifting in the mammalian system, in yeast the same frame is reached by -2 frameshifting. Two bases are read twice. The -2 frameshifting is likely to be mediated by slippage of mRNA and re-pairing with the tRNA in the P-site. The downstream pseudoknot stimulates frameshifting by 30-fold compared with 2.5-fold in reticulocyte lysates. When the length of the spacer between the shift site and the pseudoknot is extended by three nucleotides, +1 and -2 frameshifting become equal.